The Geriatric Nutritional Risk Index Predicts Postoperative Outcomes in Bladder Cancer: A Propensity Score-Matched Analysis. Issue 4 (2nd April 2022) - Riveros, Carlos; Jazayeri, Seyed Behzad; Chalfant, Victor; Ahmed, Ferdous; Bandyk, Mark; Balaji, K. C.
Abstract : Purpose: The Geriatric Nutritional Risk Index (GNRI) is a simple screening tool to predict nutrition-related risk of morbidity and mortality in older patients. We assessed whether preoperative GNRI was associated with 30-day complications after radical cystectomy (RC). Materials and Methods: Using the American College of Surgeons National Surgical Quality Improvement Program database, we identified patients 65 years or older who underwent RC for the treatment of bladder cancer between 2007 and 2019. Patients were dichotomized into at-risk (GNRI ≤98) or no-risk (GNRI >98) groups. Using propensity score matching, the 2 groups were compared for baseline differences and 30-day outcomes. We evaluated GNRI as an independent predictor of postoperative complications using multivariable logistic regression analysis. Results: We identified 2, 926 patients eligible for analysis. After propensity score matching, patients in the at-risk GNRI group had higher rates of any complication (p=0.017), blood transfusion (p=0.002), extended length of stay (p=0.004) and nonhome discharge (p <0.001). Multivariable logistic regression analysis revealed that a decreasing GNRI is an independent prognostic factor for mortality (OR 1.05, 95% CI 1.01–1.08, p=0.009), blood transfusion (OR 1.03, 95% CI 1.02–1.04, p <0.001), pneumonia (OR 1.04, 95% CI 1.01–1.07, p=0.013), extended length of stay (OR 1.03, 95% CI 1.02–1.05, p <0.001) and nonhome discharge (OR 1.04, 95% CI 1.03–1.06, p <0.001). Conclusions: We demonstrate that nutritional status evaluated by GNRI predicts 30-day complications after RC.